ANALISIS PENGEMBANGAN PARIWISATA HALAL PANTAI MENRALO DAN PANTAI AMMANI KABUPATEN PINRANG - Muhammad Nur; Ismail Hasan; Muhammad Nasri Katman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
he purpose of this study was to find out how far the development of halal tourism in Pinrang Regency, especially on Menrola Beach and Ammani Beach. The method used in this study is a qualitative method, the characteristic of this research lies in the purpose of describing a case by understanding the meaning and symptoms, so that the data analysis used is descriptive analytical. The results of the study indicate that the development of halal tourism in Pinrang Regency has great potential. Halal tourism facilities at Menralo Beach and Ammani Beach attractions are quite good in terms of the number of worship facilities provided at tourist sites such as mosques, prayer rooms, water and bathrooms. The problem that existed at Menralo Beach and Ammani Beach was that there were no processed food products provided that obtained halal certificates from LPPOM MUI.